Propagation of Economic Shocks from the United States, China, the European Union, and Japan to Selected Asian Economies: Does the Global Value Chain Matters? - Hendrati, Ignatia Martha; Heriqbaldi, Unggul; Esquivias, Miguel Angel; Setyorani, Bekti; Jayanti, Ari Dwi (International Journal of Energy Economics and Policy, 2023)
A panel vector autoregression (VAR) model is employed to estimate whether growth shocks from the United States (US), China, Japan, and the European Union (EU) can be transferred to selected Asian countries. We examine 1) the effect of shocks through five channels: international trade, monetary policy, finance, global uncertainty, and oil prices; 2) whether a country’s deeper integration with the global value chain (GVC) enhances or decreases the effect of growth shocks from major economies more intensively than trade openness. We found evidence of the shock transfer from major economies to Asia through the five channels. The impact differs across countries depending on their participation in GVC; for example, the impact is high in Indonesia and low in South Korea. Moreover, Asian countries are more exposed to trade shocks through China’s trade channel than other major economies. Zooming in on the channels’ impacts, global uncertainty affects countries’ growth (e.g., Indonesia) more significantly than other channels (i.e., GVC); and Asian countries respond positively to oil prices in the short run but negatively in the long run.